JAK inhibitors for the treatment of VEXAS syndrome. Issue 5 (May 2023) - Bindoli, Sara; Baggio, Chiara; Doria, Andrea; Bertoldo, Eugenia; Sfriso, Paolo
Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) syndrome is a novel described autoinflammatory entity for which the diagnosis is defined by somatic mutations of the UBA1 X-linked gene in hematopoietic progenitor cells. The clinical manifestations are heterogeneous since they range from autoinflammatory symptoms to the presence of underlying hematologic disorders such as myelodysplastic syndromes. Response to treatment in VEXAS is very poor and to date, the therapeutic strategies adopted are only partially effective. However, recently described cohorts of subjects with VEXAS treated with Janus kinase inhibitors (JAK-I) proved that these drugs can be effective in the treatment of several manifestations related to the disease. Herein, we carried out a brief literature review that includes cohorts and single cases in which JAK-I were adopted as a promising strategy to manage VEXAS patients. Subsequently, we described our experience with JAK-I in VEXAS, illustrating the first case, to our knowledge, of a 65-year-old man who was successfully treated with the selective JAK-1 inhibitor filgotinib.